G23(P) Increasing Rates of Complicated Chickenpox presenting to a Paediatric ED – Should Emergency Departments have a wider role in Disease Surveillance?. (7th April 2014) - Blackburn, F; Sharpe, D; Ross, J
Abstract : Aims: This study sets out to demonstrate an increase in the number of children with chickenpox, complicated by secondary infection or neurological symptoms, presenting to a large Paediatric Emergency Department (PED). This data can be contrasted against the current surveillance data, collected by sentinel GP practices, suggesting no change in the rate of uncomplicated chickenpox. If such a difference could be demonstrated it would suggest both an increasing morbidity associated with a common childhood illness and the need to review current surveillance strategies, with the PED playing a key role. Methods: Attendances to the PED in the eleven years prior to 1 st November 2013 were analysed for a diagnosis of chickenpox or Varicella. Cases identified were then interrogated via electronically recorded notes and discharge summaries to identify complications secondary to chickenpox. The nature of the complication and treatment required were recorded. Results: In the ten years prior to 1 st November 2012 22 children with complicated chickenpox presented to PED and 12 were admitted. In comparison, in the one year after the 1 st November 2012 26 children presented and 18 were admitted. Of these latter 26 cases, 93% were due to a suspected secondary bacterial infection (although an organism was identified in only 2 cases). The remaining 7% had neurological complications. No children were admitted to PICU, but 4 required HDU care. Conclusion: This data tells a very different story to data collected in primary care with a more than 10 fold increase in presentations demonstrated. While data from one centre is not in itself significant, this data suggests an increase in the morbidity attached to chickenpox and warrants review at a larger level. If this data were supported by other studies, it could re-open the debate surrounding the introduction of the chickenpox vaccine. In addition, this data suggests that the PED should have a central role in national disease surveillance.